Lifestyle Intervention for Breast Cancer Women - Hwang, Eun Suk (J Lifestyle Med, 2019)
Breast cancer patients have various physical, psychological health risks, among which are the effects on general health. Lifestyle intervention involving nutrition education, physical activity, and stress management, and has been shown to be effective in improving the health of breast cancer patients. Therefore, it is necessary to develop and apply a lifestyle intervention program to promote health in breast cancer patients.